Coated vanadium dioxide-doped thin film and preparation method and application thereof

Through the preparation method of coated doped vanadium dioxide film, the film has high phase transition temperature, low transmittance and poor weather resistance, and the film performance with high transmittance, low phase transition temperature and strong weather resistance is achieved, which is suitable for intelligent energy-saving windows.

CN119775816APending Publication Date: 2025-04-08HUBEI UNIV OF TECH +1

Patent Information

Application Number
CN202411904765.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously reduce the phase transition temperature of the vanadium dioxide film, improve its visible light transmittance and enhance weather resistance, resulting in problems such as low quality, excessive phase transition temperature, poor optical performance and poor weather resistance in practical applications.

Method used

The preparation method of the coated doped vanadium dioxide film was adopted, and the VO2 core-shell nanopowder was formed by the sol-gel method combined with the special atmosphere sintering, and mixed with the doped precursor body fluid. After coating, film formation, drying and annealing treatment, a coated doped vanadium dioxide film with high transmittance, low phase transition temperature and strong weather resistance was obtained.

Benefits of technology

It achieves high transmittance of the film, close to room temperature and strong weather resistance, and is suitable for thermally chromic smart energy-saving windows, with a long service life and can withstand various extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775816A_ABST
    Figure CN119775816A_ABST
Patent Text Reader

Abstract

The invention relates to a coated doped vanadium dioxide film and a preparation method and application thereof. The preparation method comprises the following steps: preparing a precursor vanadium solution by taking a first vanadium source and a first reducing agent as raw materials; adding a first film-forming agent and a doping agent, fully reacting, and performing aging treatment to obtain a doped precursor liquid; preparing a dispersion liquid from the M-phase VO2 nano-powder, adding a coating material precursor into the dispersion liquid, and reacting to prepare VO2 core-shell nano-powder; and uniformly mixing the VO2 core-shell nano powder and the doped precursor liquid to obtain a VO2-based coating, and carrying out coating film forming, drying and annealing treatment to obtain the coated doped vanadium dioxide film. According to the invention, through doping modification, the film has high transmittance, the phase change temperature is reduced, the core-shell structure effectively enhances the weather resistance of the material, under the combined action of doping and modification, the performance of the obtained film is effectively improved, and the film can be applied to thermochromic intelligent energy-saving windows and is long in service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of thin film materials, and in particular to a coated doped vanadium dioxide thin film and a preparation method and application thereof. Background Art

[0002] Vanadium dioxide (VO 2 ) is a typical thermotropic phase change material that changes from monoclinic VO to 2 (M) (low temperature state) to tetragonal VO 2 (R) (high temperature state) reversible metal-insulator transition (MIT). The two crystal forms are almost the same in terms of visible light transmittance, while in the near-infrared (NIR) region, they show a transition from high transmittance to high reflectivity. This feature makes VO 2 It has important application potential in the fields of smart windows, infrared detection and information transmission. However, according to previous studies, VO 2 The critical temperature of phase change of intrinsic materials is about 68 °C, and the visible light transmittance of the film is generally low due to the influence of the preparation method, which is still a certain distance away from the room temperature conditions required for practical applications.

[0003] VO 2 Among thermotropic phase change materials, the phase change temperature (68°C) is the closest to room temperature. In order to achieve application, the phase change temperature needs to be controlled to around 30°C. 2 Due to the limitation of materials in phase transition temperature, element doping, stress regulation, crystal defect regulation, grain size regulation and other methods are often used to reduce the phase transition temperature, among which element doping is a very important and effective method. 2 When high-valent ions are doped into the lattice, the phase transition temperature decreases; when low-valent ions are doped, the phase transition temperature increases. 2 The exact mechanism of phase transition temperature remains controversial.

[0004] +4 VO 2 It is in the middle valence state, has unstable thermodynamic properties, and is easily oxidized by the external environment. 2 It does not meet the requirements for the use of phase change materials. Therefore, how to improve VO 2 Weather resistance is crucial.

[0005] For VO 2The preparation of thin films requires a reasonable design method. The previous preparation methods mainly focused on different deposition processes, such as pulsed laser deposition, vapor deposition, magnetron sputtering, sol-gel method, etc. The invention of CN109437303A provides a preparation method of high-energy laser pulsed magnetron sputtering, which is currently widely used. VO2O3 is deposited on the surface of the pretreated metal substrate in a magnetron chamber with high argon and low oxygen. 2 Thin film, then continue to deposit SiO 2 Single sphere layer plasma etching to obtain micro-nanostructured VO 2 layer, although the VO prepared by this method 2 The thin film structural units are compact and have high purity, but the operation is complicated and the cost investment is high.

[0006] Therefore, the current technology is difficult to modify the material during the preparation of vanadium dioxide, cannot solve the problem of film crystallinity, and the raw materials are complicated to use, the cost investment is high and it is not suitable for large-scale production, which seriously hinders the actual use of the prepared products. 2 There are still several problems in the practical application of thin films: (1) Low film quality: Preparation of VO 2 The crystallinity of the film is difficult to control, and the uniformity will affect the sensitivity and stability of the phase change characteristics. Non-uniform films will result in inconsistent light transmission effects; (2) The phase change temperature is too high: VO 2 The phase change temperature of the film should be close to room temperature so that the indoor temperature can be adjusted under the ambient temperature; (3) The optical performance needs to be improved: the visible light transmittance of the material is not ideal, and it is necessary to ensure that it does not affect the indoor lighting effect during use. The film needs a larger solar modulation efficiency to significantly adjust the temperature; (4) The film has poor weather resistance: in the changes of daily environment, the product life is short and is greatly affected by various environmental factors.

[0007] So far, people have adopted many methods to solve the above problems, but they can only improve one aspect of the film performance, and it is still difficult to solve the multiple problems that need to be overcome in practical applications at the same time, especially it is impossible to effectively reduce VO 2 The film phase transition temperature maintains improved visible light transmittance while also having strong weather resistance. Summary of the invention

[0008] The purpose of the present invention is to overcome the above technical deficiencies, provide a coated doped vanadium dioxide film and its preparation method and application, and solve the problem that the prior art cannot take into account both VO 2 Technical issues of film phase transition temperature, visible light transmittance and weather resistance.

[0009] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a method for preparing a coated doped vanadium dioxide film, comprising the following steps: (1) preparing a precursor vanadium solution using a first vanadium source and a first reducing agent as raw materials; then adding a first film-forming agent and a doping agent, and obtaining a doping precursor solution after sufficient reaction and aging treatment; (2) Set the M phase to VO 2 Nanopowder is made into dispersion liquid, and coating material precursor is added into the dispersion liquid to react and obtain VO 2 Core-shell nanopowders; (3) VO 2 The core-shell nanopowder is mixed evenly with the doping precursor liquid to obtain VO 2 The base coating is subjected to film-forming, drying and annealing treatment to obtain a coated doped vanadium dioxide film.

[0010] In a second aspect, the present invention provides a coated doped vanadium dioxide film obtained by the above preparation method.

[0011] In a third aspect, the present invention provides an application of the above-mentioned coated doped vanadium dioxide film in thermochromic intelligent energy-saving windows.

[0012] Compared with the prior art, the beneficial effects of the present invention include: The present invention makes the film have higher transmittance and lowers the phase transition temperature through doping modification. The core-shell structure effectively enhances the weather resistance of the material. 2 Core-shell nanopowders are mixed with doping precursor liquid to obtain VO 2 The coated doped vanadium dioxide film obtained by coating, drying and annealing is a doped VO 2 The core-shell thermochromic film has high crystallinity and good uniformity. Under the joint action of the doping component and the coating component, the performance of the obtained film is effectively improved, so that it has high transmittance, a phase change temperature close to room temperature, and high doping efficiency. It can be applied to thermochromic intelligent energy-saving windows, has a long service life, can withstand various extreme environments, and can still be used normally after weathering treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 To prepare the coated doped VO in the present invention 2 Schematic diagram of the process flow of thin film samples; Figure 2 Preparation of coated doped VO for the present invention 2 Schematic diagram of the film structure; Figure 3 The coated doped VO with different Mo doping amounts prepared in Example 1 of the present invention 2SEM images of the thin film samples, where the Mo doping amounts in each figure are: (a) 1 at%, (b) 2 at%, (c) 3 at%, (d) 4 at%; Figure 4 The coated doped VO prepared in Example 2 of the present invention 2 XRD and Raman spectra of the film samples, where (a) is XRD and (b) is Raman spectra; Figure 5 The Mo-doped VO prepared in Example 1 of the present invention with a concentration of 4 at% is coated. 2 Phase change spectrum of thin film samples; Figure 6 The Nb doping concentration of 6 at% coated VO prepared in Example 2 of the present invention is 2 Phase transition spectrum of thin film samples; Figure 7 The XRD test spectra of the thin film samples prepared in Example 1 of the present invention and Comparative Example 1 are compared, wherein (a) is Example 1, and (b) is Comparative Example 1; Figure 8 The TEM test spectra of the thin film samples prepared in Comparative Example 1 and Example 1 of the present invention are compared; wherein (a) and (b) are Comparative Example 1, and the scales are 1 μm and 500 nm, respectively; (c) and (d) are Example 1, and the scales are 1 μm and 500 nm, respectively; Fig. 9 The DSC spectra of the film samples prepared in Example 1 and Comparative Example 1 of the present invention are compared in the tolerance test, wherein (a) is Comparative Example 1 and (b) is Example 1. DETAILED DESCRIPTION

[0014] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0015] The present invention provides a coated doped vanadium dioxide film and a preparation method thereof. In the method, by improving the doping and coating operations and combining the two, the coated particles are continuously coated on the doped film material, and the intrinsic VO is solved by doping. 2 The higher phase transition temperature and lower visible light transmittance bottlenecks in thin film materials are also overcome by the intrinsic VO 2 Nanoparticles are coated to improve VO 2 The weather resistance of the film enables the finished film to achieve high-quality performance of high transmittance, low phase change temperature and strong weather resistance at the same time.

[0016] The preparation method of the present invention uses a more easily operable liquid phase method, which has the advantages of being able to accurately control the proportion of reaction raw materials and reaction time, being easy to dope, and being able to form films on a large scale. Specifically, a precursor film is prepared by a sol-gel method, and then a subsequent annealing step is used to obtain a film product with high crystallinity, excellent optical properties, and good weather resistance. Unlike the traditional annealing step, the subsequent annealing step used in the present invention is carried out in a tubular furnace with a vacuum pump, but an ammonia environment created by a homemade reaction is added. The coating structure in the invention is prepared by the experimental steps, and then added to the previously prepared precursor liquid, so that the coating structure is well combined with the doping system.

[0017] First, see Figure 1 The present invention provides a method for preparing a coated doped vanadium dioxide film, comprising the following steps: (1) preparing a precursor vanadium solution using a first vanadium source and a first reducing agent as raw materials; then adding a first film-forming agent and a doping agent, and obtaining a doping precursor solution after sufficient reaction and aging treatment; (2) Set the M phase to VO 2 Nanopowder is made into dispersion liquid, and coating material precursor is added into the dispersion liquid to react and obtain VO 2 Core-shell nanopowders; (3) VO 2 The core-shell nanopowder is mixed evenly with the doping precursor liquid to obtain VO 2 The base coating is subjected to film-forming, drying and annealing treatment to obtain a coated doped vanadium dioxide film.

[0018] Preferably, in step (1), the molar ratio of the first vanadium source to the first reducing agent is (1.5-4):1; the first vanadium source includes one of vanadium pentoxide, vanadium acetylacetonate, vanadium sulfate and vanadium acetate; and the first reducing agent includes one or more of hydrazine hydrochloride, anhydrous glucose, methanol, oxalic acid, acetic acid and hydrogen peroxide.

[0019] Further preferably, the molar ratio of the first vanadium source to the first reducing agent is (2-4):1; the first vanadium source includes vanadium pentoxide, vanadium acetylacetonate or vanadium acetate; and the first reducing agent includes hydrazine hydrochloride, oxalic acid or methanol.

[0020] Preferably, in step (1), the pH value of the precursor vanadium solution is between 2 and 6, and the concentration of vanadium ions in the precursor vanadium solution is between 0.1 and 0.4 mol / L.

[0021] It can be understood that during the preparation of the precursor vanadium solution, the first vanadium source and the first reducing agent can be dissolved in deionized water A and stirred at 20 to 65° C. for 20 to 60 min to obtain the precursor vanadium solution; during the stirring process, the first catalyst is added to adjust the pH value of the precursor vanadium solution to 2 to 6; and then deionized water B is selectively added according to the situation to adjust the concentration of vanadium ions therein.

[0022] Further preferably, the first catalyst includes concentrated hydrochloric acid, acetic acid, citric acid or tartaric acid. The first catalyst can be selectively added according to the situation. For example, if the first reducing agent itself can make the solution acidic or weakly acidic, the first catalyst may not be added, or may be selectively added to promote the reaction and reduce the aging time.

[0023] Preferably, in step (1), the first film-forming agent includes polyvinyl pyrrolidone (PVP), polyvinyl butyral (PVB) or polyvinyl alcohol; the addition ratio of the first film-forming agent is 2-10% of the total mass of the precursor vanadium solution. Considering the performance factor, the present invention preferably uses PVP-K30 and PVB as film-forming agents, which have good chemical stability and strong adhesion, and the preferred addition amount is about 4-8 wt% of the total mass of the precursor vanadium solution, at which time the film-forming effect is the best.

[0024] Preferably, in step (1), the doping element in the dopant includes one or two of tungsten, molybdenum, niobium, rubidium, magnesium and fluorine; and the doping amount of the doping element is 0.5 to 20 at% of the molar amount of vanadium in the vanadium source.

[0025] Preferably, in step (1), the reaction time is 2 to 3 hours; and the aging treatment is performed in a closed light-free environment for 1 to 3 days.

[0026] Preferably, in step (2), the M phase VO 2 The nanometer powder is prepared by using the second vanadium source and the second reducing agent as raw materials through a ball milling method or a hydrothermal method.

[0027] Further preferably, in step (2), the molar ratio of the second vanadium source to the second reducing agent is (0.3-10):1; the second vanadium source comprises one of vanadium pentoxide, vanadyl acetylacetonate, vanadyl sulfate and vanadyl acetate; and the second reducing agent comprises one or more of hydrazine hydrochloride, anhydrous glucose, methanol, oxalic acid, acetic acid and hydrogen peroxide.

[0028] Further preferably, the second vanadium source includes vanadium pentoxide or vanadyl sulfate; and the second reducing agent includes oxalic acid dihydrate, acetic acid or hydrogen peroxide.

[0029] Further preferably, in step (2), the ball milling method is to ball mill the mixture of the second vanadium source and the second reducing agent for 0.5 to 1.5 hours, and then wash and dry to obtain M phase VO 2 Nano powder.

[0030] Further preferably, in step (2), the hydrothermal method is to dissolve the second vanadium source and the second reducing agent in deionized water, perform hydrothermal reaction at 160-300 °C for 1-3 days, and obtain M-phase VO by washing and drying. 2 Nano powder.

[0031] More preferably, the molar ratio of vanadium elements in the first vanadium source and the second vanadium source is (0.125-3):1, and more preferably (0.125-1.5):1.

[0032] Preferably, in step (2), the dispersion is M phase VO 2 The nano powder, alcohol solvent and the second film-forming agent are mixed; the pH value of the dispersion is 8.5-9.5.

[0033] Further preferably, in step (2), the pH value of the dispersion is adjusted to 8.5-9.5 by a second catalyst; the second catalyst includes concentrated aqueous ammonia, sodium hydroxide solution, potassium hydroxide solution or sodium bicarbonate solution. The second catalyst is used to adjust the pH and accelerate the reaction, and can be added selectively.

[0034] Further preferably, in step (2), the second film-forming agent comprises polyvinyl pyrrolidone (PVP), polyvinyl butyral ester or polyvinyl alcohol; the addition ratio of the second film-forming agent is M phase VO 2 0-10% of the total mass of nanopowder and alcohol solvent.

[0035] Preferably, in step (2), the coating material precursor includes one or more of APTES, tetraethyl orthosilicate, polydiacetylene or polyacrylate polymers, and the added amount accounts for 1-10 wt% of the mass of the dispersion.

[0036] Preferably, in step (2), after adding the coating material precursor to the dispersion, react for 4 to 6 hours to obtain VO 2 Core-shell nanopowder.

[0037] Preferably, in step (3), VO 2 The core-shell nanopowder is added to the doping precursor liquid to make VO 2 Core-shell nanopowders are directly added to the doping precursor solution, or VO 2 The core-shell nanopowder is mixed with an ethanol solution and then added into a doping precursor solution.

[0038] Preferably, in step (3), the annealing treatment is carried out in an atmosphere of ammonia, argon or nitrogen at a temperature of 400 to 650 °C for 0.5 to 3 h. In the high-temperature annealing step, oxygen-free calcination is required, and an inert gas is used instead of a vacuum environment during the calcination process, because this method consumes less energy, is more convenient to operate, and has lower equipment requirements. The precursor does not react with the inert gas, and the impurity elements in the precursor will also escape in the form of gas at high temperature and be discharged from the tubular furnace along with the flowing inert gas. It is more preferred to use a reducing atmosphere such as ammonia to ensure that the vanadium is not oxidized.

[0039] Preferably, during the annealing process, a sintering atmosphere reagent is added; the sintering atmosphere reagent includes ammonium bicarbonate and calcium oxide in a mass ratio of 1:10. It is more convenient to meet the annealing atmosphere requirements by reacting ammonium bicarbonate and calcium oxide powder at high temperature to generate ammonia.

[0040] Preferably, the glass substrate is quartz glass or borosilicate glass, SiO 2 The mass fraction is greater than 80%, and the transmittance is greater than 92%. In the process of cleaning the substrate, two or three of anhydrous ethanol, methanol, acetone and deionized water need to be recycled. The substrate of the present invention can withstand very high temperatures, has high compressive strength and tensile strength, and has unique optical properties. It needs to be cleaned with acetone and methanol before use and stored in anhydrous ethanol solution.

[0041] Preferably, the coating method includes spray coating, spin coating or blade coating, and drying is performed after coating. The coating and drying can be selectively repeated as needed, and the number of coating layers determines the thickness of the film.

[0042] In a second aspect, the present invention provides a coated doped vanadium dioxide film obtained by the above preparation method.

[0043] See also Figure 2 The coated doped vanadium dioxide film prepared by the present invention is actually doped with VO 2 Composite VO on thin film array 2 Core-shell nanoparticles improve film performance under the combined action of doping components and coating components.

[0044] In a third aspect, the present invention provides an application of the above-mentioned coated doped vanadium dioxide film in thermochromic intelligent energy-saving windows.

[0045] The present invention obtains a doped VO 2Core-shell thermochromic films have high transmittance and can be used in thermochromic smart energy-saving windows. Among them, "smart windows" are a new type of energy-saving means that uses special dimming materials combined with glass substrates to dynamically control indoor and outdoor heat exchange. By adjusting solar radiation, the indoor temperature is controlled to reach the most comfortable human body temperature range, thereby reducing the energy consumption of indoor cooling and heating to achieve energy saving. This technology uses color-changing materials with variable optical properties, which can change their optical properties (such as transmittance, reflectivity, absorptivity, etc.) according to different physical stimuli (such as light, electricity, gas, heat, etc.), thereby achieving controllable adjustment of indoor ambient temperature. In contrast, thermochromic materials have the advantages of low cost, simple structure and fully automatic photothermal modulation. They have received increasing attention due to their passive response characteristics and are ideal for the next generation of smart windows. Vanadium dioxide (VO 2 ) The unique thermoinduced phase transition phenomenon at the critical temperature is accompanied by significant changes in optical and electrical properties. The visible light transmittance remains almost unchanged before and after the thermoinduced phase transition, but the transmittance in the near-infrared band changes significantly, which can effectively take into account both lighting and energy saving, making it very suitable for smart window applications. 2 Energy-saving materials have not been put into production yet, mainly because they cannot take into account VO 2 Thin film phase transition temperature, visible light transmittance and weather resistance. The present invention proposes the above solution to address the deficiencies in phase transition temperature, light transmittance and weather resistance, thereby providing a feasible path for the practical application of vanadium dioxide-based smart windows.

[0046] The main mechanism of action of the present invention: (1) Optimization of film preparation atmosphere: In the present invention, the sol-gel method used is combined with a method of subsequent annealing of special atmosphere sintering. The precursor obtained by the action of hydrochloric acid hydrazine and concentrated hydrochloric acid is essentially tetravalent vanadium, so high-temperature sintering needs to be carried out in an oxygen-free environment. The sintering process is usually carried out in a tubular furnace. The traditional process of creating an oxygen-free atmosphere in a furnace generally uses a high-performance vacuum pump to extract as much gas as possible from the tubular furnace to achieve a vacuum environment close to the ideal state. The advantage of this solution is that it can eliminate the interference of all gas factors, and the obtained film is only related to the film itself and the sintering temperature; the disadvantage is that evacuating the air requires a high-performance vacuum pump and a long waiting time, and the energy consumption is extremely high.

[0047] Taking all factors into consideration, the above solution is difficult to implement and consumes a lot of equipment and resources. It is impossible to ensure that the relative pressure and vacuum degree of each experiment are consistent. Therefore, the air is replaced by inert gas. Inert gas such as N is continuously introduced into the tube furnace. 2, Ar, etc., to replace the air environment with inert gases to achieve a relative absolute vacuum. The advantages of this solution are low energy consumption, easy operation, and low equipment requirements; the precursor does not react with the inert gas, and the impurity elements in the precursor will also escape in the form of gas at high temperature, and will be discharged from the tube furnace along with the flowing inert gas, and finally the target product, pure phase vanadium dioxide film, will be obtained. But it also has a disadvantage that at higher temperatures, the N 2 May participate in the reaction. Therefore, based on the inert gas, the ammonia environment is preferred. Ammonia is a reducing gas, NH 3 The film annealing under the environment can ensure the prepared VO to the greatest extent. 2 The film is not oxidized, so that the vanadium ions always exist in the sample in the form of +4 valence, thus ensuring a higher purity of the sample.

[0048] (2) Film performance optimization: VO 2 The biggest difficulty in putting thin films into practical application is to modify their intrinsic properties. The material has a high phase transition temperature, low visible light transmittance, and low tolerance. To solve these problems, commonly used improvement methods include doping, multilayer structure design, microstructure design and other means. After trying to use element doping combined with coated particle coating, the most significant effect on performance was found. There are many choices for doping elements. The present invention uses molybdenum, niobium, rubidium, magnesium, fluorine and other elements. They are close to the periodic position of V ions and have the most suitable ionic radius and ionic valence, which can easily achieve the doping effect. The coating material of the present invention uses APTES, silica, polydiacetylene or polyacrylate polymers, which have the advantage of being compatible with VO 2 It has strong polymerization ability and good compatibility with the doped film.

[0049] (3) Extended product life: The present invention can well simulate the sample state of the experimental sample when it is used in actual scenarios, and is a highly reliable experimental method for the engineering implementation of the sample.

[0050] (4) In the present invention, a reducing agent is used to reduce the vanadium source. Excessive catalyst accelerates the reaction and adjusts the pH. The formation of the precursor liquid requires a sufficiently long reaction time. During the color change of the solution, the vanadium ions are reduced from pentavalent to tetravalent. The valence states of molybdenum, niobium and other ions are higher than those of vanadium ions, and their larger ionic radius makes them very easy to join the lattice. The concentration of the substance in the liquid can be adjusted by adding water to the fixed volume; high-purity M-phase VO 2 The nanopowders are formed by reaction in a high pressure hydrothermal reactor or ball mill. The core-shell structure is obtained by 2 The nanopowder is covered with a highly light-transmitting inert shell.

[0051] In summary, the film and preparation method obtained by the present invention have the following advantages: (1) Excellent film quality: high crystallinity, good uniformity, no agglomeration; the film color is light brown transparent film, and the film thickness is in the range of 60-90 nm; (2) The phase transition temperature is close to room temperature and the doping efficiency is high; (3) Good optical properties: The material is transparent, chemically stable, with a visible light transmittance of about 60%, good lighting effect, high infrared modulation efficiency, and can significantly lower the indoor temperature; (4) Long service life, able to withstand various extreme environments, and can still be used normally after tolerance treatment; (5) The various functional groups on the surface of the coating material are compatible with the polymer resin material, which is more conducive to film formation, easy to prepare and low cost.

[0052] The present invention is further described in detail below through specific embodiments and comparative examples; the prepared quartz glass has a size of 1.5 cm×1.5 cm×1.0 mm, is cleaned with acetone and methanol, and is stored in anhydrous ethanol; the instruments used are all existing instruments, mainly including an electronic balance (JE-203GE), an electric digital display constant temperature water bath (HH-2), a constant temperature digital display magnetic stirrer (B13-3), a CNC ultrasonic cleaning machine (KQ-300DE), a blast drying oven (BPG-9156A), a vacuum drying oven (DZF-6050), a deionized water purifier (Master-Q), a desktop high-speed centrifuge (TG16-WS), and a high-energy ball mill.

[0053] Example 1 (1) Dissolve 5.5 g (30 mmol) of vanadium pentoxide and 1.6 g (15 mmol) of hydrazine hydrochloride in 50 ml of deionized water and stir in a water bath at 60 °C for 30 min. Add 25 ml of concentrated hydrochloric acid (38 wt%) dropwise to adjust the pH value to 4. Continue stirring for 30 min and then add deionized water to adjust the vanadium ion concentration in the solution after the reaction to 0.3 mol / L to obtain a precursor vanadium solution. Then, add PVP accounting for 6 wt% of the total mass of the precursor vanadium solution and molybdenum chloride with doping concentrations of 1 at%, 2 at%, 3 at%, and 4 at% of the molar amount of vanadium element, respectively, and stir for three hours. Then age for 1 day to obtain a doped precursor solution.

[0054] (2) Weigh 1.83 g (10 mmol) V 2 O 5 With 0.182 g (1 mmol) DC 6 H 12 O 6The mixture was added to a zirconia ball mill, and the zirconia grinding balls were added and ground using a high-energy ball mill for 1 h. The obtained product was washed three times with a mixed liquid of anhydrous ethanol / deionized water in a volume ratio of 1:1, placed in a 45 °C environment, vacuum dried for 12 h, and carefully ground using an agate mortar to obtain M phase VO 2 Nano powder.

[0055] Towards M phase VO 2 100 mL of anhydrous ethanol and 1 mL of deionized water were added to the nanopowders, and ultrasonic dispersion was performed for 1 h to obtain a dispersion. APTES accounting for 3 wt% of the total mass of the dispersion was then added. The dispersion was reacted at ambient temperature using magnetic stirring. After 5 h, the nanopowders were centrifuged and washed twice with anhydrous ethanol. The nanopowders were dried in a vacuum oven at 45 °C for 12 h and ground using an agate mortar to obtain VO 2 @APTES core-shell nanopowder.

[0056] (3) The obtained VO 2 @APTES core-shell nanopowder is directly added to the doping precursor liquid, ultrasonically dispersed and stirred evenly to obtain VO 2 The coating was sprayed on quartz glass with a spray gun and dried at 60 °C. The coated film was placed in a tube furnace and annealed at 550 °C for 1 h after adding 0.1 g of ammonium bicarbonate and 1 g of calcium oxide powder. The coated vanadium dioxide film was obtained: Mo-doped VO 2 Core-shell thermochromic films.

[0057] Example 2 (1) 0.66 g (2.5 mmol) of vanadium acetylacetonate and 20 mL of methanol solution (containing 0.625 mmol of methanol; if other ethanol with higher concentration is used, the final concentration of vanadium ions can also be adjusted by adding deionized water) were stirred for 30 min to obtain a precursor vanadium solution with a vanadium ion concentration of 0.125 mol / L. Then, 6 wt% PVP accounting for the total mass of the precursor vanadium solution and niobium chloride with doping concentrations of 2 at%, 4 at%, 6 at%, and 8 at% of the molar amount of vanadium element were added, stirred for 2 h, and aged for 2 days to obtain a doped precursor solution.

[0058] (2) 1.83 g (10 mmol) of vanadium pentoxide and 3.78 g (30 mmol) of oxalic acid H 2 C 2 O 4 ·2H 2O was dissolved in 50 mL of deionized water and stirred in a 60 °C water bath, then transferred to a polytetrafluoroethylene liner and hydrothermally heated at 280 °C for 48 h to obtain the target powder in one step. The high-purity M-phase VO was obtained after washing with deionized water and ethanol for multiple times and drying for 12 h. 2 Nano powder.

[0059] M-phase VO 2 The nanopowder was then mixed with 2 wt% PVP (in the form of M phase VO 2 5 mL of ammonia water (28 wt%) was dissolved in 50 mL of anhydrous ethanol and stirred to obtain a dispersion with a pH value of 9; 10 mL of a mixed solution of tetraethyl orthosilicate accounting for 3 wt% of the total mass of the dispersion was prepared and added to the dispersion at a rate of 0.5 mL / min. The mixture was reacted at room temperature for 12 h to obtain VO 2 @SiO 2 Core-shell nanopowder.

[0060] (3) The obtained VO 2 @SiO 2 The core-shell nanopowders were directly added to the doping precursor solution and ultrasonically dispersed and stirred to obtain VO 2 The film was sprayed on quartz glass with a spray gun and dried at 60 °C. The film was placed in a tube furnace and annealed at 500 °C for 1 h with 0.1 g of ammonium bicarbonate and 1 g of calcium oxide powder. The coated vanadium dioxide film was obtained: Nb-doped VO 2 Core-shell thermochromic films.

[0061] Example 3 The only difference from Example 1 is that in step (1), the molybdenum chloride doping concentration is 4% of the molar amount of vanadium element, and in step (2), APTES is replaced by polydiacetylene or polyacrylate. The other steps and conditions are the same as in Example 1.

[0062] The results show that replacing the coating material precursor with polydiacetylene or polyacrylate has little effect on the results, and the prepared film performance is close to that of the film in Example 1. This shows that polydiacetylene or polyacrylate polymers can also have good compatibility with the doped film.

[0063] Comparative Example 1 The only difference from Example 1 is that step (2) is removed and the doping concentration of molybdenum chloride is fixed. The other steps and conditions are the same as those in Example 1 to obtain a doped VO without a coating material. 2 ; Specifically including the following steps: 5.5 g of vanadium pentoxide and 1.6 g of hydrazine hydrochloride were dissolved in 50 ml of deionized water and stirred in a water bath at 60 °C for 30 min. 25 ml of concentrated hydrochloric acid (38 wt%) was added dropwise to adjust the pH value to 4. After continuing to stir for 30 min, deionized water was added to adjust the vanadium ion concentration in the solution after the reaction to 0.3 mol / L to obtain a precursor vanadium solution. PVP accounting for 6 wt% of the total mass of the precursor vanadium solution and molybdenum chloride with a doping concentration of 4 at% were added and stirred for three hours. The mixture was aged for 1 day to obtain a doped precursor liquid.

[0064] The doping precursor liquid was sprayed on the quartz glass using a spray gun and dried at 60 °C. The film was placed in a tube furnace and annealed at 550 °C for 1 h after adding 0.1 g of ammonium bicarbonate and 1 g of calcium oxide powder. Mo-doped VO 2 Thermochromic film, denoted as Mo-VO 2 .

[0065] Comparative Example 2 The only difference from Example 2 is that step (1) is removed, and the other steps and conditions are the same as those in Example 2 to obtain an undoped coated VO 2 The film comprises the following steps: 1.83 g of vanadium pentoxide and 3.8 g of oxalic acid were dissolved in 50 mL of deionized water and stirred in a 60 °C water bath. The mixture was transferred to a polytetrafluoroethylene liner and hydrothermal treated at 280 °C for 48 h. After washing and drying for 12 h, high-purity M-phase VO was obtained. 2 Nano powder.

[0066] M-phase VO 2 The nanopowder was then dissolved in 50 mL of anhydrous ethanol with 2 wt% PVP and 5 mL of ammonia (28 wt%) to obtain a dispersion. 10 mL of a mixed solution of 3 wt% tetraethyl orthosilicate was prepared and added to the dispersion at a rate of 0.5 mL / min. The mixture was reacted at room temperature for 12 h to obtain VO 2 Base coating.

[0067] Use a spray gun to 2 The base coating was sprayed on quartz glass and dried at 60 °C. The film was placed in a tube furnace and annealed at 500 °C for 1 h with 0.1 g of ammonium bicarbonate and 1 g of calcium oxide powder. 2 Core-shell thermochromic film, denoted as VO 2 @SiO 2 .

[0068] Comparative Example 3 The only difference from Example 2 is that step (2) is removed and the niobium doping concentration is fixed to 6 at% of the molar amount of vanadium element. The other steps and conditions are the same as those in Example 2 to obtain an uncoated Nb-doped VO 2 Finally, Nb-doped VO 2 Thermochromic film, denoted as Nb-VO 2 .

[0069] Effect Characterization First, for VO 2 There are complete parameter indicators to evaluate its advantages and disadvantages: phase transition temperature ( T c )、Visible light transmittance( T lum ), solar energy regulation efficiency (Δ T sol ), weather resistance. Phase transition temperature ( T c ) refers to VO 2 The temperature at which a reversible semiconductor-metal phase transition occurs, VO 2 The intrinsic T c is 68 ℃, which needs to be close to room temperature (25 ℃) in practical applications; visible light transmittance ( T lum ) refers to the comprehensive integral of the transmittance of smart energy-saving windows in the visible light band (380-780 nm). Visible light transmittance is a key parameter that determines indoor lighting performance. T lum A high value indicates good indoor lighting performance; conversely, a low value indicates poor lighting performance. The first condition to be met in practical application is T c Close to room temperature (25 ± 5℃), and secondly, the maximum visible light transmittance ( T vis ) has certain requirements (preferably more than 60%). Solar energy regulation efficiency (Δ T sol ) refers to the ability of smart energy-saving windows to regulate sunlight, and refers to the difference in the integrated transmittance of the film in the ultraviolet to near-infrared band (350-2600 nm) of sunlight when the film is in a low-temperature state and a high-temperature state. The higher the value, the stronger the ability to regulate indoor temperature; conversely, the lower the value, the weaker the ability to regulate indoor temperature. T lum ) and solar regulation efficiency (Δ T sol ), usually calculated using the following formula: (1) in,T (λ) represents the transmittance of sunlight at wavelength λ, φ lum (λ) represents the sensitivity of the human eye to sunlight with a wavelength of λ, φ sol (λ) represents the radiation intensity of sunlight at a wavelength of λ.

[0070] Example 1 of the present invention prepares coated VO with different molybdenum doping amounts 2 The SEM test results of film embodiment 1 are as follows Figure 3 As shown in the figure, the finished nanoparticles are evenly distributed, the morphology is uniform, and the film quality is good. With the increase of molybdenum doping amount, the doping makes VO 2 The particle size of the film is reduced (from 64.49nm to 60.69nm). 2 The optical performance data of the film was obtained by using a Hitachi UH-4150 UV-Vis-NIR spectrometer and integrating the above formula, and is summarized in Table 1 below.

[0071] Table 1 Optical properties of the film obtained in Example 1

[0072] It can be seen from Table 1 that VO doped with 3 at% Mo 2 The film exhibits excellent T vis (56.3%). In addition, Mo doping can adjust VO 2 The phase transition temperature of the film, T c As the Mo concentration changes, it reaches -9.7 k / at%, and the Mo-doping amounts of 3 at% and 4 at% are closest to room temperature. Figure 5 As shown. At the same time, molybdenum doping can adjust the width of the thermal hysteresis loop. Therefore, in the present invention, the preferred molybdenum doping amount is 1 to 4 at% of the molar amount of vanadium in the vanadium source, and more preferably 3 to 4 at%.

[0073] Example 2: Preparation of coated VO with different Nb doping concentrations with high transmittance and enhanced thermochromic properties 2 The test results of the film are shown in Table 2.

[0074] Table 2 Optical properties of the film obtained in Example 2

[0075] As shown in Table 2, all the thin film samples prepared in Example 2 have high visible light transmittance and direct solar transmittance. 2 The film has a narrower thermal hysteresis loop width and excellent phase change ability, such as Figure 6 As shown in Figure 2, when the niobium doping content reaches 6 at%, the phase transition temperature T c =28.5 ℃ is close to room temperature, and the film T lum =52.1% and T sol =60.6 %, which can well meet the practical application. Therefore, in the present invention, the preferred niobium addition amount is 2-8 at% of the molar amount of vanadium in the vanadium source, further preferably 6-8 at%, and more preferably 6 at%; and the overall performance of Example 2 is better than that of Example 1, which can simultaneously meet the relevant requirements of phase transition temperature and maximum visible light transmittance, so the present invention preferably adds niobium.

[0076] Uncoated Mo-doped VO was prepared by comparative example 1. 2 film, and the coated Mo-doped VO in Example 1 2 For the weather resistance treatment of the experimental samples, the present invention adopts a method of simulating scene loss. The specific operation is to prepare the coated Mo-doped VO 2 Film and uncoated Mo-doped VO in Comparative Example 1 2 The film was placed in a 60 °C oven, and 500 mL of deionized water was placed between the two films. The water source was changed every 12 hours and heated and dried for 120 hours. The treated film was subjected to XRD, TEM and DSC tests to detect the weather resistance of the film. After a series of such special environmental operations, the sample state of the experimental sample in actual scenarios can be well simulated. It is a highly reliable experimental method for the engineering implementation of the sample. The results are as follows Figure 7-Figure 9 shown.

[0077] like Figure 7 As shown, the XRD spectrum shows that the core-shell structure is doped with VO 2 Film (a) shows clear VO 2 The characteristic peaks of the M phase are not present, and there is no impurity peak; while there is no core-shell structure of doped VO 2 Film (b) has no protective layer and is directly exposed to air for oxidation, so there is a little V 2 O 5 The results preliminarily prove that the core-shell structure is doped with VO 2 Film (a) has strong weather resistance; Figure 8 As shown, TEM characterization revealed that, compared with Comparative Example 1 (a, b), after coating, the morphology of Example 1 was as shown in (c, d), and a few branches appeared in its morphology, which was related to the addition of the coating material.

[0078] observe Fig. 9The DSC images show that before weathering treatment, Mo-doped VO 2 and coated Mo-doped VO 2 Obvious heat flow difference peaks appeared in both the heating and cooling processes, indicating that the sample underwent phase change at this temperature. Fig. 9 As shown, Example 1 coated Mo doped VO 2 (b) The peak intensity of the heat flow difference is reduced, but the phase change ability is still maintained; while the uncoated Mo-doped VO in Example 1 2 (a) The phase change ability has been completely lost. The weather resistance of the film after coating has been greatly improved, and it has excellent anti-oxidation and anti-corrosion capabilities, and can effectively work for a long time in a hot and humid environment.

[0079] Undoped VO was prepared by comparative example 2. 2 film, and Nb-doped VO in Example 2 2 Comparison of core-shell thermochromic films. Figure 4 As shown in the XRD (a) comparison results, the crystal peak of the doped film has a blue shift, and the Nb 3d The spectra collectively indicate the addition of Nb element.

[0080] Uncoated doped VO was prepared by Comparative Examples 1 and 3. 2 The film is compared with the undoped coated VO prepared in Comparative Example 2. 2 The results are shown in Table 3.

[0081] Table 3 Film properties of Comparative Examples 1-3

[0082] From Table 3 and the observed UV transmission spectrum and thermal hysteresis loop of the test, it is found that the transmittance of the film of Comparative Example 2 is lower than that of Comparative Example 1 and Comparative Example 3. At the same time, the phase transition temperature of the film of Comparative Example 2 is 72.5°C, which is much lower than that of the film after doping modification, and the optical performance is worse than that of the film after doping modification.

[0083] Through Example 1 and Example 2, it is found that the implementation steps of the present invention can effectively combine the excellent indicators of doping and coating, and can meet the required multiple performance requirements. The prepared coated doped VO 2 The film can maintain a suitable phase transition temperature and high visible light transmittance while also taking into account strong environmental weather resistance. Combining the above experimental results, it can be found that the coated VO after Mo doping and Nb doping 2 The film has better optical properties and stronger weather resistance. 2The core-shell structure is more compatible with Nb doping, and elements with a valence state closer to the V ion and the element period can better adapt to the coating structure. 2 The visible light transmittance of the film changes slightly after adding the core-shell structure, among which the Nb-doped coated film has a higher transmittance, reaching a maximum visible light transmittance of more than 65% ( T vis ), and the phase change ability and weather resistance are not affected, and the prepared samples can meet the standards of practical application.

[0084] In summary, the present invention prepares high-quality VO with good uniformity and crystallinity. 2 The doping modification makes the film have a higher transmittance and reduces the phase transition temperature (the visible light transmittance of the film is greater than 40%, T c The core-shell structure effectively enhances the weather resistance of the material (the phase change ability is less affected by the environment). The film prepared by the present invention can well meet the practical application requirements of modern smart windows, with low cost, simple process and suitable for industrial production.

[0085] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a coated doped vanadium dioxide film, characterized in that: The following steps are involved: (1) preparing a precursor vanadium solution using a first vanadium source and a first reducing agent as raw materials; Then, a first film-forming agent and a doping agent are added, and after sufficient reaction, an aging treatment is performed to obtain a doping precursor liquid; (2) preparing a dispersion of M-phase VO2 nanopowder, adding a coating material precursor to the dispersion, and reacting to obtain VO2 core-shell nanopowder; (3) The VO2 core-shell nanopowder is uniformly mixed with the doping precursor liquid to obtain a VO2-based coating, and the coating, film-forming, drying and annealing treatment are performed to obtain a coated doped vanadium dioxide film.

2. The method for preparing a coated doped vanadium dioxide thin film according to claim 1, characterized in that: In step (1), the molar ratio of the first vanadium source to the first reducing agent is (1.5-4):1; The first vanadium source includes one of vanadium pentoxide, vanadyl acetylacetonate, vanadyl sulfate and vanadyl acetate; The first reducing agent includes one or more of hydrazine hydrochloride, anhydrous glucose, methanol, oxalic acid, acetic acid and hydrogen peroxide.

3. The method for preparing a coated doped vanadium dioxide thin film according to claim 1, characterized in that: In step (1), the pH value of the precursor vanadium solution is between 2 and 6, and the concentration of vanadium ions in the precursor vanadium solution is between 0.1 and 0.4 mol / L; The first film-forming agent includes polyvinyl pyrrolidone, polyvinyl butyral ester or polyvinyl alcohol; the addition ratio of the first film-forming agent is 2-10% of the total mass of the precursor vanadium solution; The doping elements in the dopant include one or two of tungsten, molybdenum, niobium, rubidium, magnesium and fluorine; the doping amount of the doping elements is 0.5-20% of the molar amount of vanadium in the vanadium source.

4. The method for preparing a coated doped vanadium dioxide thin film according to claim 1, characterized in that: In step (1), the reaction time is 2 to 3 hours; and the aging treatment is performed in a closed light-free environment for 1 to 3 days.

5. The method for preparing a coated doped vanadium dioxide thin film according to claim 1, characterized in that: In step (2), the M-phase VO2 nanopowder is prepared by a ball milling method or a hydrothermal method using a second vanadium source and a second reducing agent as raw materials; The molar ratio of the second vanadium source to the second reducing agent is (0.3-10): 1; The second vanadium source includes one of vanadium pentoxide, vanadyl acetylacetonate, vanadyl sulfate and vanadyl acetate; The second reducing agent includes one or more of hydrazine hydrochloride, anhydrous glucose, methanol, oxalic acid, acetic acid and hydrogen peroxide.

6. The method for preparing a coated doped vanadium dioxide thin film according to claim 5, characterized in that: The molar ratio of vanadium elements in the first vanadium source and the second vanadium source is (0.125-3):

1.

7. The method for preparing a coated doped vanadium dioxide thin film according to claim 1, characterized in that: In step (2), the dispersion is obtained by mixing M-phase VO2 nanopowder, alcohol solvent and a second film-forming agent; the pH value of the dispersion is between 8.5 and 9.5; The second film-forming agent includes polyvinyl pyrrolidone, polyvinyl butyral ester or polyvinyl alcohol; the addition ratio of the second film-forming agent is 0-10% of the total mass of the M-phase VO2 nanopowder and the alcohol solvent; The coating material precursor includes one or more of APTES, tetraethyl orthosilicate, polydiacetylene or polyacrylate polymers, and the added amount accounts for 1-10 wt% of the mass of the dispersion; After adding the coating material precursor into the dispersion, the VO2 core-shell nanopowder is prepared by reacting for 4 to 6 hours.

8. The method for preparing a coated doped vanadium dioxide thin film according to claim 1, characterized in that: In step (3), the annealing treatment is carried out in an atmosphere of ammonia, argon or nitrogen at a temperature of 400 to 650° C. for 0.5 to 3 h.

9. The coated doped vanadium dioxide thin film obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the coated doped vanadium dioxide film as claimed in claim 9 in thermochromic intelligent energy-saving windows.

Citation Information

Patent Citations

  • Thermochromic intelligent thermal-control device based on VO2 film and preparation method of thermochromic intelligent thermal-control device

    CN109437303A

Cited By

  • Core-shell structure composite powder with vanadium dioxide coated with calcium fluoride and preparation method

    CN121108773A